Fungsi Badan Permusyawaratan Desa (BPD) dalam Pembentukan Peraturan Desa di Desa Sanding Kecamatan Tampaksiring Kabupaten Gianyar - Agus Leo Adi Wibawa; Ida Ayu Putu Widiati; A.A. Sagung Laksmi Dewi (Jurnal Konstruksi Hukum, 2021)
BPD has the task of making rules with the village head, taking and proposing community ideas, therefore the BPD as a deliberation body originating from the village community, in addition to carrying out its duties as an intermediary between the village head and the village community, also carries out its main function, namely the function of representation. The purpose of this research is to reveal the function of the Village Consultative Body in the formation of Village Regulations and the obstacles to implementing the functions of the Village Consultative Body in the formation of Village regulations in Sanding Village, Tampaksiring District, Gianyar Regency. The type of research used is empirical legal research using a sociological juridical approach. The data collection technique was carried out by field research. The data sources used are primary and secondary which are then analyzed systematically and linked to other legal materials. The results of the research reveal that the functions of the Village Consultative Body in forming the Village Regulations include, among others, being able to prepare and propose draft Village Regulations. Draft Village Regulations can be proposed by members of the BPD to the leadership of the Village Consultative Body to be determined as a draft Village Regulation proposed by the BPD. Barriers to the implementation of functions in the formation of village regulations, namely, first, juridical obstacles include: Lack of knowledge and experience of BPD members, understanding of the laws and regulations regarding villages of BPD members, many BPD members with low levels of education and secondly, non-juridically, namely the presence of BPD members in the preparation and understanding of the legal basis for the formation of village regulations is still low and the application potential of the village is also low.